Um estudo sobre a saúde mental de Serra-ES : da surpresa ao encantamento - Rossoni, Cláudia Gomes (2006)
This research studies the directed conditions of the modeling used in the organization of the Mental Health Service on Serra District that has in the Mental Health Team of the Regional Health Unities, an extra-hospital service for the reorientation of the attendance model. Qualitative research consummated through a case study that has with data collection method, the Focal Group. Five Focal Groups are realized with the mental health team professionals, in October to December months of 2005 and the data had been analyzed in its content, on the basis of Bardin. It classifies the directed conditions that shape the mental health service in two modalities: constituted and constituent. The constituted ones, of the municipal politics of mental health, are the ones that point the line of direction technician-administrative politics, and the constituent, the ones that are related to the social practices developed in the daily of the health institution for the mental health professionals, from the processes lived deeply for these actors in the relation with the territory and the demand in health. It concludes that the implanted service has potentialities and contributions for the reorientation of the attendance model. It detaches that the consisting conditions had been important for the creation and consolidation of the mental health service, but is centered in the constituent conditions the modeling of this service, therefore it is in the daily relation between its actors who if become possible to introduce new forms to deal with the psychic suffering and to construct a new culture in mental health. For in such a way, the magnifying of a net of mental health and one politics of permanent education of its professionals for the appropriation of the territory is necessary and attendance of the demands in health. To catch these phenomena was important to recognize the potentialities of the service in the consummation of the politics of mental health of the city and to apprehend its limits and perspectives.